Prevalence of permethrin-resistant kdr mutation in head lice (Pediculus humanus capitis) from elementary school students in Jeddah, Saudi Arabia - Alsaady,Isra M.; Altwaim,Sarah; Gattan,Hattan S.; Alghanmi,Maimonah; Zawawi,Ayat; Ahmedah,Hanadi; Wakid,Majed H.; Azhar,Esam I. (PeerJ, 2023)
Head lice (Pediculus humanus capitis) are a major global concern, and there is growing evidence of an increase in head lice prevalence among Saudi schoolchildren. The purpose of this study is to investigate the prevalence of an insecticidal resistance mutation in head lice collected from schoolchildren. A polymerase chain reaction (PCR) was used to amplify a segment of the voltage-gated sodium channel gene subunit to assess the prevalence and distribution of the kdr T917I mutation in head lice. Subsequently, the restriction fragment length polymorphism (RFLP) patterns revealed two genotypic forms: homozygous-susceptible (SS) and homozygous-resistant (RR). The results showed that 17 (37.80%) of the 45 samples were SS, whereas 28 (62.2%) were RR and T917I and L920F point mutations were found in the nucleotide and amino acid sequences of RR. Compared to other nations, the frequency of permethrin resistance mutation in the head louse population in Saudi Arabia was low. This study provides the first evidence of permethrin resistance mutation in human head lice in Saudi Arabia. The findings of this study will highlight the rising incidence of the kdr mutation in head lice in Saudi Arabia.
Keywords: Pyrethroid resistance; Head lice (Pediculus humanus capitis)